Perlaksanaan program pembangunan staf di sekolah islam hidayah, Johor Bahru - Mad Arip, Hafsah (2013)
his descriptive study seeks the perception of teachers towards the effectiveness of professional development program among school staff in a private religious school using the mixed method. Data were gathered from 97 respondents who were teachers of Sekolah Rendah Islam Hidayah (SRIH) and Sekolah Menengah Islam Hidayah (SMIH) in Pusat Pendidikan Hidayah (PPH). The questionnaires that were used and distributed were divided into five parts which are aimed to retrieve information regarding the respondents’ background, the effectiveness through the aspect of knowledge development, the effectiveness of professional development program through the aspect of skills development, the effectiveness through the aspect of attitude development and other things which can affect the effectiveness of the program. The research instrument has been tested to identify its reliability according to Alpha Cronbach scale towards 20 teachers of the same school. The result of the pilot study showed a high reliability value item which is 0.848. Research data is analyzed through Statistical Package For The School Science (SPSS) Version 16.0 program to get the mean, percentage and standard deviation. The findings showed that mean value of the whole parts were very high level and means that majority of teachers agreed that professional development program effect in the aspects of knowledge development, skills development and shaping the teachers’ attitude. In addition, interviews have been conducted with two teachers in PPIH to support the findings gained through questionnaire. Through the analysis, professional development program was able to help teachers in academic, and to implement Tarbiyya dan Dakwah to raise the attitude of pupils. Finally, a few suggestions for further study have been propose for future research.